CENTRAL INLAND FISHERIES RESEARCH STATION, CALCUTTA—ANNUAL REPORT FOR THE YEAR 1953 - Mandapam, CMFRS (Indian Journal of Fisheries, 2016)
During the year under review, the headquarters of this Research Station was shifted from Barrackpore to Calcutta as a temporary measure till such time as the proposed laboratory and hostel buildings at Barrackpore are constructed. The Riverine and Lacustrine Section was shifted to Allahabad. The Motor Launch Bhetki was used for fishery investigations in the estuarine areas. The year under report registered substantial progress in the programmes of work, both in the field and in the laboratory.